Methods of preserving the environment in Islamic law - Mahmoud, Prof. Dr. Mahmoud Abdullah Mahmoud; Pajani, M. M. Karwan Abdul Rahman Ali Pajani; Othman, M. Sarwat Ahmed Othman (Sulaimani Journal for Humanities, 2025)
The environment is the framework that surrounds humans and living organisms, providing them with essential elements for life, such as air, water, and soil. Therefore, preserving it is essential for sustaining life and maintaining ecological balance. It is a trust that must be safeguarded, and Islamic teachings emphasize the prohibition of corruption on earth, the protection of natural resources, and the proper treatment of all living beings. This research explores the means of environmental preservation in Islam, addressing the increasing environmental challenges that necessitate examining the solutions provided by Islamic teachings to maintain ecological balance. The significance of this study lies in highlighting the values and legislations in Islam that contribute to environmental protection and in promoting environmental awareness. The selection of this topic is driven by the growing environmental crises and the need to implement Islamic principles in addressing them. The study aims to clarify the concept of environmental preservation in Islam, review the religious texts that advocate for it, and demonstrate the impact of adhering to Islamic teachings in reducing environmental problems. The research adopts a deductive approach based on Islamic texts, in addition to a descriptive-analytical method to study Islamic teachings related to the environment and benefit from previous studies.The research plan is structured as follows: an introduction that outlines the general framework of the topic, followed by a prelude highlighting the importance of the environment from an Islamic perspective. The first chapter then examines the means of environmental preservation, such as the prohibition of corruption on earth, water conservation, afforestation, animal welfare, and public cleanliness. The second and final chapter discusses the impact of adhering to these regulations on environmental protection and the role of individuals and communities in achieving sustainable development. The study concludes with findings and recommendations that emphasize the importance of applying Islamic teachings to preserve the environment.
Keywords: Means; Protection; Islamic law; Environment